Enhanced Photocatalytic Degradationof Rhodamine-BDye using Photocatalyst ZNO Sensitized by Visible Light - Shadia Farhan Abd, Hassan Abbas Alshamsi, (Pakistan Journal of Medical & Health Sciences, 2022)
In the current study, zinc oxide nanoparticles in different concentrations were synthesized by environmentally friendly biosynthesis method using Argyreia nervosa leaf extract and used to remove Rhodamine-B dye. The structure, optical activity, morphology and porosity of the obtained nanomaterials were determined using different techniques including These include X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), elemental spectroscopy (EDX), and scanning electron microscopy (TEM), and fluorescence imaging. ultraviolet. The reflection spectroscopy (DRS) and Brunauer-Emmett-Teller (BET), and the zinc oxide chemical bond formations were confirmed by FT-IR, then the XRD results showed that the zinc oxide nanoparticles were successfully synthesized. TEM images of (ZnO-NPs) showed that the majority of the particles were spherical and weakly agglomerated, the best RhB stain removal was approached under ideal conditions (RhB = 5 ppm,10ppm,15ppm, pH = 11, catalyst dose = 1.4 g/L and time irradiation = 180 minutes). The high efficiency of the catalyst showed enhanced photocatalytic behavior for the degradation of RhB dye with a removal rate (48% ) at 5ppm concentration, at a concentration of 10ppm about 31% and at concentration 15ppm the decomposition efficiency is 19%, without using any metal doping Keywords: green synthesis, ZnO, Photodegradation, RhodamineB, Argyreia nervosa, mechanism.